1977
DOI: 10.1113/jphysiol.1977.sp012063
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative description of the pattern of breathing during steady‐state CO2 inhalation in man, with special emphasis on expiration

Abstract: SUMABLY1. Quantitative data on the pattern of breathing in normal men and women (Gardner, 1977)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

1977
1977
1993
1993

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
0
27
1
Order By: Relevance
“…Experiments in man and animals have demonstrated that chemical stimuli can influence inspiration and expiration independently (Drysdale & Ward, 1976;Eldridge, 1976;Gardner, 1977;Cunningham & Gardner, 1977;Ward & Cunningham, 1977). The effects of a change in q in the present experiments on phrenic motoneurone output can satisfactorily be accounted for by relating Ti and Phr to the chemical events at the carotid body during inspiration and also by relating Re to the events occurring during expiration.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Experiments in man and animals have demonstrated that chemical stimuli can influence inspiration and expiration independently (Drysdale & Ward, 1976;Eldridge, 1976;Gardner, 1977;Cunningham & Gardner, 1977;Ward & Cunningham, 1977). The effects of a change in q in the present experiments on phrenic motoneurone output can satisfactorily be accounted for by relating Ti and Phr to the chemical events at the carotid body during inspiration and also by relating Re to the events occurring during expiration.…”
Section: Discussionmentioning
confidence: 49%
“…The independent effect of Phr on Ti and Te suggest that separate functional mechanisms are involved in the control of the two phases of the respiratory cycle, at least in the vagotomized dog. The findings have some resemblance to those obtained in conscious man when ventilation was stimulated either by alternate breath oscillations of alveolar PCo2 (Drysdale & Ward, 1976), or by steady-state CO2 inhalation (Gardner, 1977;Cunningham & Gardner, 1977). It may be relevant to note that in conscious man in eupnoea, there is no evidence of any vagal control of breathing (Guz, Noble, Widdicombe, Trenchard, Mushin & Makey, 1966).…”
Section: Discussionmentioning
confidence: 65%
“…The most consistent functions for locating the breakpoint were PA, co, VS. VT (high oxygen points only) and VT/TI versus VT, both of which were usually bilinear (see Gardner, 1975;Cunningham & Gardner, 1977). The discontinuity between the two lines in both plots corresponded well with the breakpoint as estimated by eye from the volume-time plots.…”
Section: Location Of Breakpointmentioning
confidence: 75%
“…In general, for man, the inspiratory part of the pattern of ranges 1 and 2 shown on the right of Fig. 1 Hey et al (1966) is presented in a companion paper (Cunningham & Gardner, 1977). Some of this work has appeared in abstract form (Cunningham & Gardner, 1972;Gardner, 1975 (VG-Micromass Ltd, Winsford, Cheshire, England).…”
Section: Introductionmentioning
confidence: 99%
“…However, other authors have shown in animals that, whereas a major component of the ventilatory response is mediated via the arterial chemoreceptors, a significant component is the result of direct effects on the central nervous system (Eldridge & Gill-Kumar, 1980;Winn et al, 1979). Folgering (1980) (Hey et al, 1966;Cunningham & Gardner, 1977;Gardner, 1977 (Bailey, 1959).…”
Section: Introductionmentioning
confidence: 99%